Os percursos dos atores Lavo, Mundo e Jano: A enunciação e o enunciado em Cinzas do Norte - Moscardini, Miriam (2010)
This work analyses the novel Cinzas do Norte by Milton Hatoum. The theory which underlies our analysis is the French semiotics. The study aims at verifying how the dysfunctional relation between the main character “Mundo” and his father “Jano” is established, considering the value each one of them gives to their objects of value. For this, we resorted to the study of passions, in special the passion of anger and its variants, based on A. J. Greimas and J. Fontanille‟s studies. Another aim is to verify the point of view of “Lavo”, the narrator of the novel, who relates in the present of the enunciation, the story of his friend Mundo. Furthermore, through Lavo‟s perspective as a simulacrum of the enunciator and as a participant actor, we examine how he reconstructs the protagonist‟s course, delegating voice to the other narrators. This textual strategy enables the creation of truth effect of sense to the text. We also examine the strategies used by the enunciator when he changes not only his point of observation but also the delegation of voice. Moreover, we finally examine the anchoring of the text in the north of the country and in the military dictatorship context. Besides, we looked for the effects of sense produced in the text by means of the spatial and temporal anchoring just like the pluri-isotopic character of the figure “ashes” in Hatoum‟s novel.